2006
DOI: 10.1007/s11259-006-3278-4
|View full text |Cite
|
Sign up to set email alerts
|

Economically Important Non-oncogenic Immunosuppressive Viral Diseases of Chicken—Current Status

Abstract: Immunosuppressive viral diseases threaten the poultry industry by causing heavy mortality and economic loss of production, often as a result of the chickens' increased susceptibility to secondary infections and sub-optimal response to vaccinations. This paper aimed to present an up-to-date review of three specific economically important non-oncogenic immunosuppressive viral diseases of chickens, viz. chicken infectious anaemia (CIA), infectious bursal disease (IBD) and hydropericardium syndrome (HPS), with emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 156 publications
(149 reference statements)
0
21
0
Order By: Relevance
“…Immunosuppressive diseases usually negatively affect chickens of the poultry industry by increasing the susceptibility to opportunistic infections by viruses and bacteria (Lutticken, 1997;Balamurugan & Kataria, 2006). Among the known immunosuppressive agents, CAV stands out for its worldwide occurrence, not only in commercial poultry, but also in SPF chickens (Schat, 2003;Balamurugan & Kataria, 2006), backyard chickens (Barrios et al, 2009), as well as contaminates poultry vaccines (Barrios et al, 2012). CAV presents tropism for T-lymphocytes, rendering the cellular immune response ineffective, especially in young chickens, by destroying CD8+ T cells (Adair et al, 1993;Adair, 2000;Brentano, 2009), disabling the protection against intracellular agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunosuppressive diseases usually negatively affect chickens of the poultry industry by increasing the susceptibility to opportunistic infections by viruses and bacteria (Lutticken, 1997;Balamurugan & Kataria, 2006). Among the known immunosuppressive agents, CAV stands out for its worldwide occurrence, not only in commercial poultry, but also in SPF chickens (Schat, 2003;Balamurugan & Kataria, 2006), backyard chickens (Barrios et al, 2009), as well as contaminates poultry vaccines (Barrios et al, 2012). CAV presents tropism for T-lymphocytes, rendering the cellular immune response ineffective, especially in young chickens, by destroying CD8+ T cells (Adair et al, 1993;Adair, 2000;Brentano, 2009), disabling the protection against intracellular agents.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that the MG F-strain vaccine may cause disease in the upper respiratory tract of chickens, which is possibly exacerbated when a concomitant secondary infection is present (Lin & Kleven, 1982;Yoshida et al, 2000). Natural coinfections may occur in the field, under appropriate conditions, with vaccine strains, as well as with wild and more virulent strains, potentially causing more significant productivity losses (Balamurugan & Kataria, 2006;Javed et al, 2005). Vaccines against CAV in breeders and MG in layers are commercially available in Brazil and the impact of the respective diseases may be reduced through vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Direct losses of poultry are linked to specific mortality because of recent 're-emergence' of the IBDV in the form of antigenic variants and hypervirulent strains. The indirect economic impact of the disease is also considerable, due to virus-induced immunosuppression and/or potential interactions between IBDV and other viruses, bacteria or parasites (Balamurugan and Kataria, 2006). These indirect losses are due to secondary infections, growth retardation and poor immune response to vaccines (Kibenge et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Immunosuppressive diseases usually negatively affect chickens in the poultry industry by increasing their susceptibility to opportunistic infections by viruses and bacteria (Balamurugan & Kataria, 2006). Immunosuppression in chickens can be induced by many viruses, including MDV, ALV, REV and CAV (chicken anemia virus), which cause similar lesions, making their diagnosis in the field more difficult .…”
Section: Naturally Occurring Co-infection Of Avian Leukosis Virus (Sumentioning
confidence: 99%